Students’ perceptions towards the integration of knowledge management processes in M-Learning Systems: A preliminary study - Al-Emran, Mostafa; Mezhuyev, Vitaliy; Adzhar, Kamaludin (TEMPUS Publications, 2018)
It is highly important for the higher educational institutions to understand the factors that affect the students’ acceptance of Mobile Learning (M-learning) systems as a prior step to the implementation of such systems. From the M-learningperspective, the literature ignores some f actors that could contribute to improve the knowledge acquisition, sharing, application, and protection, and how such factors could affect the M-learning acceptance. From the Knowledge Management (KM) perspective, research shows that KM processes have a positive impact on the acceptance an implementation of many Information Systems (IS). We observed that the existing literature overlooks the impact of KM processes on M-learning acceptance. Accordingly, the main objective of this study is to analyse the students’ perceptions towards the integration of KM processes in M-learning systems. A mixed method (questionnaire and interviews) was used for data collection. An online survey has been sent to IT undergraduate students in two different universities in two different regions namely, Universiti Malaysia Pahang (UMP) in Malaysia and Al Buraimi University College (BUC) in Oman. 305 students responded to the survey. Results indicated that around 74% of students reported that it is interesting to incorporate KM processes in M-learning systems. Additionally, results pointed out that 93% of the students indicated that they would use the M-learning system in their studies if all KM processes will be taken into consideration. It is imperative that these results will assist the M-learning systems developers to take these factors into their consideration while designing and developing such systems. Furthermore, educators may need to elaborate their teaching strategies in a way that suits ths use of these systems and meets the students’ needs.